2015
DOI: 10.5489/cuaj.2972
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and outcomes of organ-sparing surgery for testicular tumour with benign tendency

Abstract: Introduction: We retrospectively investigated and summarized our experiences and the outcomes of organ-sparing surgery (OSS) for testicular tumour with benign tendency. Methods: From April 2000 to March 2012, 11 selected patients with testicular tumour underwent OSS. Preoperative and postoperative organ functional and oncologic indexes were analyzed and compared. Results: All operations were completed without conversion to radical orchiectomy. Intraoperative frozen section and routine postoperative pathology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It has also been shown that organ sparing surgery is a reasonable and reliable alternative for testicular tumors with benign tendency. 16 Preservation of the testicular function holds importance in terms of preventing the postoperative erectile dysfunction (ED). ED is seen in 31.5% of patients after radical orchiectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that organ sparing surgery is a reasonable and reliable alternative for testicular tumors with benign tendency. 16 Preservation of the testicular function holds importance in terms of preventing the postoperative erectile dysfunction (ED). ED is seen in 31.5% of patients after radical orchiectomy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Liu et al reported no significant changes between preoperative and postoperative sperm concentrations and motilities in 11 patients with TSS history due to benign testicular tumors. 16 The risk of recurrence in the contralateral testis in patients with who had malign testicular tumors was reported to be between 1.8% and 2.8%. 20 The most common bilateral testicular tumor is seminoma that can present with metachronous metastasis in 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…İkincisi, bu kitlelerde canlı tümör varlığını öngören iyi bir görüntüleme keşfedilmiştir: 18-fluoro-deoxyglucose positrson emission tomografi (FDG-PET). FDG-PET ve tümör belirteçleri kullanılarak kemoterapi sonrası RPLND kararı Günümüzde intraoperatif frozen biyopsi olanağının yaygın kullanılmaya başlaması, dikkatli hasta seçimi ve yakın takip ile bazı testis tümörleri fonksiyonel testis dokusu bırakmak adına organ koruyucu cerrahi ile tedavisi bildirilmiştir (29,30). Çalışmamızda psikolojik ve kozmetik etkileri göz önünde bulundurularak preoperatif değerlendirme sonrasında benign karakter taşıyan beş olguya testis koruyucu cerrahi uygulanmıştır.…”
Section: Discussionunclassified
“…Moreover, it has been reported that unilateral orchiectomy has disruptive effects on overall spermatogenesis (4). Liu et al reported no significant changes in terms of sperm concentrations and motility in 11 patients with TSS history for benign testicular tumors (12).…”
Section: Introductionmentioning
confidence: 99%